Pengaruh Pemberdayaan, Pelatihan, Dan Kerjasama Tim Terhadap Kinerja Pegawai Smk Merdesa Di Kota Serang - Ahmad Wildan; Abdul Ajiz; Indra Edi (E-Journal Studia Manajemen, 2022)
This research aims to prove that empowerment, training, and team work greatly affect the performance of SMK Merdesa Serang employees. This causal quantitative research with survey method, uses empowerment, training and team work as independent variables, and employee performance as dependent variable. Data was collected using questionnaire and analyzed using path analysis techniques. The path analysis results revealed four important findings. First, empowerment has a significant effect on employee performance. Second, training has a significant effect on employee performance. Third, team work has a significant effect on employee performance. Fourth, all variables namely empowerment, job training, and team work together has an effect on employee performance. Overall these findings confirm that the performance of SMK Merdesa Serang employees is influenced by empowerment, training, and team work environment, so that SMK Merdesa Serang are advised to use these three factors as benchmarks in an effort to improve employee performane.